Non-Cryoprecipitation Separation of Coagulation FVIII and Prothrombin Complex Proteins by Pseudoaffinity Calcium Elution Chromatography Using Anion Exchange Resin - Gabriel Pinna Feliciano; Sara Hayama Arimori; Vinicius Watanabe Nakao; Joice Rodrigues Dos Santos; Elizabeth A. L. Martins; Marcelo Porto Bemquerer; Elisabeth Cheng (MDPI AG, 2022)
Hemophilia A is treated with human plasma coagulation factor VIII (FVIII) replacement therapy and Hemophilia B with coagulation factor IX, which is purified from prothrombin complex concentrate (PCC). In this paper we evaluated the separation of FVIII and PCC by directly loading raw thawed plasma to an anion exchange resin (AEX). Under this relatively high ionic strength, most of the plasma proteins such as albumin, immunoglobulins and others were not adsorbed. Five resins commonly used in protein purification (plasma fractionation) were tested. With all resins, PCC was eluted by pseudoaffinity in a calcium gradient step. Afterwards, FVIII could be recovered with a good yield and high purification factor in the salt gradient step with 400-500 mM NaCl. Using ANX Sepharose FF and Q Sepharose FF, the CaCl2 elution step was introduced after the intermediate wash with 200 mM NaCl, whereas using DEAE Sepharose FF, Fractogel EMD TMAE and Fractogel EMD DEAD, PCC eluted after the wash of the unbound proteins. Our results indicate that three important fractions: (1) albumin, immunoglobulin etc.; (2) PCC; and (3) FVIII can be separated in one chromatographic AEX column and the delicate and troublesome cryoprecipitation can be eliminated, making the purification of blood products faster and cheaper.